Pengaruh Konversi Bank Konvensional Menjadi Bank Syariah Terhadap Minat Masyarakat Menjadi Nasabah (Studi Kasus Di Kecamatan Timang Gajah Kabupaten Bener Meriah) - Ichsan Ichsan; Lisa Fitri (LPPM, 2023)
This study aims to determine the effect of converting conventional banks into Islamic banks on public interest in becoming customers (Case Study in Timang Gajah District, Bener Meriah Regency). This study uses primary data obtained by distributing questionnaires to 100 respondents. The type of research is quantitative using non probability sampling method in the form of accidental sampling in determining the sample. The data analysis method used is simple linear regression with the help of the Statistical For Social Science (SPSS) Application Program. Partial research results show that the conversion of conventional banks into Islamic banks has a positive and significant effect on public interest in becoming customers in Timang Gajah District, Bener Meriah Regency. Judging from the adjusted R square (R2) value is 68.1% while the remaining 31.9% is influenced by other variables outside this study.